CPAA: agroforestry in Amazonia and elsewhere - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
CPAA (1) is the Amazonian agroforestry research centre of the Brazilian agricultural research corporation EMBRAPA. It was founded in 1989 with the mission to disseminate scientific knowledge and technologies aimed at the development of the western...